The Effect of Creative Application Media on Mathematical Representation Ability of Grade IV Elementary School Students - Qurratu'ain, Naurah; Kowiyah , Kowiyah (Journal of Educational Sciences, 2025)
This research was motivated by students’ difficulties in describing and visualizing mathematical concepts, particularly in plane figure material. Students also struggled to relate these concepts to real-life situations, limiting their ability to apply mathematics in everyday contexts. The research aimed to examine whether the use of the Qreatif Application Media could enhance students’ mathematical representation abilities. A quantitative approach was used with a quasi-experimental design, specifically a nonequivalent group posttest-only control design. Data were collected through tests administered to both the experimental and control classes. Data analysis involved an independent sample t-test and an effect size test. The results showed that the experimental class achieved an average score of 89.61 in mathematical representation ability, while the control class averaged 77.19. The t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. Therefore, it can be concluded that the use of the Qreatif Application Media had a positive impact on students’ mathematical representation abilities in plane figure material compared to conventional teaching methods.